PENANAMAN PENDIDIKAN KARAKTER BAGI ANAK USIA DINI MELALUI BAHASA - Berliana Fabiola Sukma; Astuti Darmayanti; Nida’ul Munafiah (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Character education must be instilled from the age of 0 in children. Character education is used to support and shape a child's personality. therefore the need for training in Early Childhood related to gender, social, emotion, religiosity, tolerance, and other characters in a balanced between cognitive and psychomotor. While this character can be formed through various things including language. Therefore the focus of this research is to instill character education in early childhood through a language bridge. The purpose of this research is to pave the way and innovation for educators in carrying out activities to educate early childhood through language. This study uses qualitative research. Data were obtained through literacy studies in the form of journal articles, books and related sites. data analysis in this research is descriptive analysis. While the results of this study are in the form of character education through language that educators need to apply through various cues such as: 1) providing education through body touch (physical touch), 2) teaching children to voluntarily serve others, 3) invite quality time to be able to discuss their problems, 4) provide requirements or limits to children regarding what is allowed and what is prohibited.